Radioimmunodetection of Malignant Melanoma with the 225.28S Monoclonal Antibody to HMW-MAA - Buraggi, G. L. (Nuklearmedizin - NuclearMedicine, 1986)
A review of the studies on the use of the antigen-antibody system HMW-MAA 225.28S in melanoma radioimmunodetection is reported. The results obtained in a pilot study (42 patients with 74 lesions), a multicenter trial (254 patients with 553 lesions) and a prospective study still outstanding (29 patients with 38 lesions) allow to consider this system as suitable for clinical application. F(ab′)2 labelled with 99mTc gave the best results in terms of positivity. Moreover this radioisotope allows the best dosimetric conditions. The gamma energy emitted by this radionuclide is particularly convenient for conventional scintillation cameras and ECT. Very good results in terms of sensitivity (70%-85%) and especially specificity (about 100%) were achieved. Possible clinical applications of the method are discussed.Ein Überblick über Studien zur Anwendung des Antigen-Antikörper- Systems HMW-MAA 225.28S zum Radioimmunnachweis des Melanoms wird gegeben. Die Ergebnisse, die in einer Pilotstudie (42 Patienten mit 74 Läsionen), einer Multicenterstudie (254 Patienten mit 553 Läsionen) und einer noch ausstehenden prospektiven Studie (29 Patienten mit 38 Läsionen) erhalten wurden, erlauben es, dieses System als geeignet für die klinische Anwendung anzusehen. F(ab′)2, markiert mit 99mTc, lieferte die besten Resultate im Hinblick auf den Positivnachweis. Darüber hinaus läßt dieses Radioisotop die besten dosimetrischen Bedingungen zu. Die von diesem Radionuklid emittierte Gamma-energie ist für konventionelle Gammakameras und ECT besonders gut geeignet. Sehr gute Resultate wurden im Hinblick auf die Sensitivität (70-85%) und besonders auf die Spezifität (gegen 100%) erhalten. Die möglichen klinischen Anwendungen dieser Methode werden diskutiert.